Psychiatric disorders and interventions in patients sustaining facial fractures from interpersonal violence - Arpalahti Annamari; Haapanen Aleksi; Auro Kirsi; Abio Anne; Snäll Johanna (United Kingdom, 2025)
Background: This retrospective study clarified patients´ psychiatric morbidity in IPV-related facial fractures; in particular, their additional psychiatric care. We hypothesized that patients in need of additional support can be identified, allowing overall care processes to be improved.
Methods: Patients' age, sex, anamnestic psychiatric disorders, history of substance abuse, and psychiatric interventions were recorded, as well as the perpetrator, location, time of day, assault mechanism, fracture type, treatment, and associated injuries.
Results: In all, 807 adult patients were included in the study. Of these, 205 patients (25.4%) had anamnestic psychiatric disorders that were associated independently with female sex (OR 1.95, 95% CI 1.12, 3.41; p = 0.019) or history of substance abuse (OR 5.82, 95% CI 4.01, 8.46; p < 0.001). Patients with anamnestic psychiatric disorder were more likely to be subjected to severe violence, with an increased risk for combination fractures (OR 2.51, 95% CI 1.30, 4.83; p = 0.006). Of all patients, 61 (7.6%) received a psychiatric intervention within the first 12 months. The most common reasons for intervention were anxiety/fear and psychotic symptoms, surfacing within one month in 57% of patients. Anamnestic psychiatric disorders (OR 2.00, 95% CI 1.04, 3.82; p = 0.036), severe mental illnesses (OR 2.45, 95% CI 1.04, 5.77; p = 0.040), and use of an offensive weapon (OR 2.11, 95% CI 1.11, 4.02; p = 0.023) were the strongest independent predictors of psychiatric intervention.
Conclusions: Our results emphasize the need for more structured treatment protocols for patients sustaining IPV injury. Special attention is recommended for patients with anamnestic psychiatric disorders, severe mental illnesses, and those assaulted with an offensive weapon.